Descriptive analysis of interpreter service mode costs & usage in Northwestern Wisconsin pre and peri COVID-19 - Elena N. Casey; Erin Fitzgerald; Hannah S. Rackers; Derek Bates; Kelson Fox; Mary Bygd (BMC Health Services Research)
Abstract Background Interpreter service mode (in person, audio, or video) can impact patient experiences and engagement in the healthcare system, but clinics must balance quality with costs and volume to deliver services. Videoconferencing and telephone services provide lower cost options, effective where on site interpreters are scarce, or patients with limited English proficiency (LEP) and/or interpreters are unable to visit healthcare centers. The COVID 19 pandemic generated these conditions in Northwest Wisconsin (NWWI). The objectives of our study were to describe visit characteristics for interpreter services pre and peri COVID-19 and how interpreter visits and costs differed by modality and language pre and peri COVID-19 at Mayo Clinic Health System (MCHS) Eau Claire and Menomonie, Wisconsin (WI). Methods We analyzed medical records and billing data from MCHS Eau Claire and Menomonie that included interpretation visit characteristics and aggregate costs. We performed descriptive analysis of visit characteristics and aggregate costs (dependent variables: cost, duration, language, modality, payer type, department, patient age, and patient biological sex) from June-December 2019, 2020 (independent variables). We used Pearson’s chi-square and t tests to test for significant differences in visit characteristics between time periods. Results Significant differences were found in distribution of all visit characteristics (language, p-value < .001; biological sex, p-value .011; mode, p-value < .001; payer type, p-value < .001; department, p-value < .001; age, p-value .016; visit duration in hours, p-value < .001) between 2019 and 2020 windows. Total costs of all interpretation modes increased between 2019 (in person, $188,109; audio, $15,734; video $15,881) and 2020 (in person, $388,500; audio, $44,376; video, $34,245) despite similar visit counts for both years (2019, 3750 visits; 2020, 3425 visits). Differences between years are consistent with COVID-19 protocols, department usage by language, and patient age. Conclusions Our results show similar counts in the number of overall visits and increase in interpreter service costs in all modes, positively reflecting upon the availability of multimodal language resources.